Volunteer Activism and Professionalism in Social-Movement Organizations - Kleidman, Robert (1994)
The effects of professionalism on volunteer activism within social movement organizations (SMOs) are more complex than generally recognized. Professionalism can inhibit or erode, substitute for, or facilitate volunteer activism. Most studies identify one of these patterns as typical of SMOs or dominant in a particular case. This article argues that some combination of the three, rather than a single pattern, is probably more typical of SMOs. To identify such combinations two analytic tools are needed: a more complex concept of volunteer activism than is generally used, and, a broader understanding of the means by which professionals influence volunteer activism. This article develops these tools through a comparative case study of the umbrella organizations of three major peace campaigns - the Emergency Peace Campaign (1936-1937), the atomic test ban campaign (1957-1963), and the nuclear weapons freeze campaign (1979-1986). The umbrella organizations are then shown to incorporate different combinations of the three basic patterns of professional-volunteer relations